Clinical and laboratory characteristics of lymphoid neoplasms in serous effusions: a single centre experience in China. Issue 12 (5th August 2020) - Gong, Xubo; Shao, Sijia; Jin, Lan; Fu, Yanbiao; Wang, Lin; Xiao, Xibin; Yang, Linjuan; Zhao, Xiaoying
Abstract: Background: Lymphoid neoplasms in serous effusions are uncommon, and the details of lymphoid neoplasms in serous effusions from China are still unclear. Methods: Between January 2004 and December 2019, all patients with lymphoid neoplasms in pleural effusions, ascites, and pericardial effusions in our hospital, were reviewed. Results: A total of 65 patients with lymphoid neoplasms were collected during this period. The top three neoplasms were diffuse large B‐cell lymphoma (DLBCL) (n = 20, 30.7%), myeloma (n = 13, 20.0%), and T‐lymphoblastic lymphoma (n = 7, 10.8%). In pleural effusions involving DLBCL, the cytomorphology of DLBCL cells was diverse; most pleural effusions were present during the tumor course (92.9%); bilateral pleural effusions were predominant (57.2%); and the median survival time was only 1.23 months after the effusion. In pleural effusions involving myeloma, 90.9% of cases (10/11) had a high ratio (> 1.0) of immature to mature plasma cells; paraprotein types of IgA (36.4%) and light chain λ (36.4%) were the most frequently found; bilateral pleural effusions were easily found (n = 10, 90.9%); and the median survival time was only 1.4 months after the effusion. Conclusion: In pleural effusions involving DLBCL, most of our patients with effusions are present during the tumor course, and bilateral pleural effusions are predominant. In pleural effusions involving myeloma, the paraprotein types of IgA and light chain λ are the most frequently found, and it has a high ratio of immature to mature plasma cells in pleural effusions.